DARI SERTIFIKASI MENUJU PEMBINAAN BERKELANJUTAN: ANALISIS KEBIJAKAN PENDIDIKAN TERHADAP GURU DALAM JABATAN DI INDONESIA - Ridha Anugrah Kahar; Nurul Annisa; Sirajuddin Saleh; Febriana Putri; Nurchalisah Zaidin; Ashfary Mukrim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Improving the quality of education is highly dependent on the quality of teachers as the main actors in the learning process. In the Indonesian context, in-service teacher development policies have largely relied on certification as an instrument for professional recognition and the improvement of teachers’ welfare. However, developments in educational policy indicate that certification alone is insufficient if it is not followed by systematic, continuous, and needs-based professional development for teachers in schools. A gap in the literature remains evident in the limited analysis that positions certification, In-Service Teacher Professional Education, learning communities, academic supervision, and continuous professional development as an interconnected policy ecosystem. This article argues that in-service teacher development policies need to be reoriented from an administrative paradigm toward a substantive paradigm that emphasizes competency improvement, reflective teaching practices, mentoring, and impact-based evaluation. Using a literature review and an educational policy analysis approach, this study finds that certification remains important as an entry point for teacher professionalization, but it should not become the ultimate goal of teacher development. The implications of this study highlight the need to strengthen post-certification development policies through needs-based training, continuous supervision, learning communities, and evaluation systems that assess real changes in teaching practices.